Peningkatan kemampuan kader dalam pendampingan ibu hamil hingga menyusui dua tahun berbasis buku KIA dan media edukasi booklet - Indrasari, Nelly; Fikri, Ahmad; Rahmadi, Antun; Khoiriyah, Yustin Nur (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The period from pregnancy to two years of age is a crucial phase in preventing stunting and improving maternal and child health. Community health cadres play a strategic role in supporting pregnant and breastfeeding mothers; however, their capacity to utilize the Maternal and Child Health Handbook (KIA) and educational media remains limited. Purpose: To improve the knowledge and role of Posyandu cadres in supporting pregnant mothers through the age of two through the use of the KIA handbook and educational booklets. Method: This community service activity was conducted in Sukamaju Village, Abung Semuli District, North Lampung Regency in 2025. The target group included Posyandu cadres, pregnant mothers, breastfeeding mothers, and families of toddlers. The activity involved 30 Posyandu cadres, 30 pregnant mothers, 30 breastfeeding mothers, and was also attended by representatives from the village government, community health centers, and village midwives. The program employed a community-based, participatory approach focused on increasing the capacity of cadres in supporting pregnant mothers through the first two years of breastfeeding through the use of the Maternal and Child Health Handbook (KIA) and educational booklets. Summative evaluation was conducted at the end of the program through observation, interviews, and assessment of changes in knowledge, attitudes, and practices of cadres and targets. Evaluation activities were conducted in the prenatal classes and integrated health posts (Posyandu) in Sukamaju Village. Results: Cadres' understanding of breastfeeding techniques increased from 22.9% before training to 88.6% after training. Cadres' ability to explain Early Initiation of Breastfeeding (IMD) increased from 31.4% to 91.4%, while their ability to conduct breastfeeding counseling based on the Maternal and Child Health (KIA) Handbook and educational media increased from 17.1% to 82.9%. Implementation results showed that 30 pregnant women received education on breastfeeding preparation for up to two years, 11 mothers received IMD assistance during delivery, and 30 breastfeeding mothers reported successful latching after counseling by the cadres. In addition, 19 mothers began practicing breast milk expression and storage according to guidelines, and 30 babies' growth monitoring was recorded in the KIA Handbook. Conclusion: Community service activities through empowering cadres to accompany pregnant women up to two years of breastfeeding based on the Maternal and Child Health (KIA) Handbook and educational media booklets have proven effective in increasing cadre capacity, as well as increasing knowledge and practices among pregnant and breastfeeding mothers. Empowering cadres based on the KIA Book is a relevant and applicable strategy in supporting stunting prevention efforts at the community level. Suggestion: It is hoped that cadre mentoring will continue and be routinely integrated into integrated health post (Posyandu) activities and prenatal classes. It is also recommended that future community service activities be longer-term and involve a wider target group so that the long-term impact on stunting prevention can be evaluated more comprehensively. Keywords: Cadre empowerment; Health education; KIA handbook; Pregnant women; Stunting prevention Pendahuluan: Periode sejak kehamilan hingga anak berusia dua tahun merupakan fase krusial dalam pencegahan stunting dan peningkatan derajat kesehatan ibu dan anak. Kader kesehatan masyarakat memiliki peran strategis dalam mendampingi ibu hamil dan menyusui; namun, kapasitas kader dalam memanfaatkan Buku Kesehatan Ibu dan Anak (KIA) serta media edukasi masih terbatas. Tujuan: Untuk meningkatkan pengetahuan dan peran kader Posyandu dalam pendampingan ibu hamil hingga anak berusia dua tahun melalui pemanfaatan buku KIA dan media edukasi booklet. Metode: Kegiatan pengabdian kepada masyarakat ini dilaksanakan di Desa Sukamaju, Kecamatan Abung Semuli, Kabupaten Lampung Utara pada tahun 2025. Sasaran kegiatan meliputi kader Posyandu, ibu hamil, ibu menyusui, serta keluarga balita. Kegiatan ini melibatkan 30 kader posyandu, 30 ibu hamil, 30 ibu menyusui dan dihadiri juga dari pemerintah desa, puskesmas, dan bidan desa. Program dilakukan dengan pendekatan community-based participatory approach yang difokuskan pada peningkatan kapasitas kader dalam pendampingan ibu hamil hingga menyusui dua tahun melalui pemanfaatan Buku Kesehatan Ibu dan Anak (KIA) dan media edukasi booklet. Evaluasi sumatif dilaksanakan pada akhir program melalui observasi, wawancara, serta penilaian perubahan pengetahuan, sikap, dan praktik kader dan sasaran. Kegiatan evaluasi dilakukan pada kelas ibu hamil dan posyandu di Desa Sukamaju. Hasil: Pemahaman kader terhadap teknik menyusui meningkat dari 22.9% sebelum pelatihan menjadi 88.6% setelah pelatihan. Kemampuan kader dalam menjelaskan IMD meningkat dari 31.4% menjadi 91.4%, sedangkan kemampuan melakukan konseling ASI berbasis Buku KIA dan media edukasi meningkat dari 17.1% menjadi 82.9%. Hasil implementasi menunjukkan bahwa 30 ibu hamil memperoleh edukasi persiapan menyusui hingga dua tahun, 11 ibu mendapatkan pendampingan IMD saat persalinan, dan 30 ibu menyusui melaporkan keberhasilan pelekatan (latch-on) setelah konseling oleh kader. Selain itu, 19 ibu mulai menerapkan praktik memerah dan menyimpan ASI sesuai panduan, serta 30 bayi tercatat lengkap pemantauan pertumbuhannya dalam Buku KIA. Simpulan: Kegiatan pengabdian kepada masyarakat melalui pemberdayaan kader pendamping ibu hamil hingga menyusui dua tahun berbasis Buku Kesehatan Ibu dan Anak (KIA) dan media edukasi booklet terbukti efektif dalam meningkatkan kapasitas kader serta pengetahuan dan praktik pada ibu hamil dan ibu menyusui. Pemberdayaan kader berbasis Buku KIA merupakan strategi yang relevan dan aplikatif dalam mendukung upaya pencegahan stunting di tingkat komunitas. Saran: Diharapkan, agar pendampingan kader dilanjutkan dan diintegrasikan secara rutin dalam kegiatan posyandu dan kelas ibu hamil. Kegiatan pengabdian selanjutnya juga disarankan memiliki durasi yang lebih panjang dan melibatkan jumlah sasaran yang lebih luas agar dampak jangka panjang terhadap pencegahan stunting dapat dievaluasi secara lebih komprehensif.